2015
DOI: 10.1111/tct.12321
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional learning on a stroke unit

Abstract: Effective interprofessional learning programmes are imperative to promote collaborative practice amongst health care professionals. Stroke units are ideal learning environments for practice-based interprofessional education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The interview guide for the semi-structured interviews was compiled by the research team (PP, JS, KF) in a consensus meeting discussing relevant content areas identified through a selective literature search on IPC, IPE, and CM (Antoni, 2010;Frisby et al, 2015;Klafke et al, 2016;Mette et al, 2016;Schärli et al, 2017;Sorbero et al, 2008). This paper reports on the answers to the following questions: Participants were recruited by means of purposive sampling, either face-to-face, by e-mail, or by telephone.…”
Section: Focus Groups and Individual Interviewsmentioning
confidence: 99%
“…The interview guide for the semi-structured interviews was compiled by the research team (PP, JS, KF) in a consensus meeting discussing relevant content areas identified through a selective literature search on IPC, IPE, and CM (Antoni, 2010;Frisby et al, 2015;Klafke et al, 2016;Mette et al, 2016;Schärli et al, 2017;Sorbero et al, 2008). This paper reports on the answers to the following questions: Participants were recruited by means of purposive sampling, either face-to-face, by e-mail, or by telephone.…”
Section: Focus Groups and Individual Interviewsmentioning
confidence: 99%
“…16 Several authors advocate for experiential IPE situated in practice-based settings. [17][18][19] Community-based education (CBE) is suggested as a model for facilitating IPE in collaborative skills in the workplace. [20][21][22] CBE is defined as learning activities that use the community extensively as a learning environment, in which not only students but also teachers, members of the community, and representatives of other sectors are actively engaged throughout the educational experience.…”
Section: Introductionmentioning
confidence: 99%
“…It also suggests that learning in real practice effectively fosters the culture that must be developed in the real situation and that learning with an IPE design will be effective if implemented in practice-based settings. [17][18][19]61 CBIPE seems a potentially effective way to stimulate interprofessional collaborative learning for students. Our research indicates that successful implementation is possible but that the role of supervisor/teacher and assessment procedures both require close attention.…”
mentioning
confidence: 99%
“…Such an approach aims to ensure that the IPE opportunities are meaningful to all participants and are placed in the context of their professional discipline. A number of examples have been presented in the literature including the work of Feltham et al (2016) in respect of student midwives and paramedic students' experiences of shared learning in pre-hospital childbirth and by Frisby et al (2015) about the effect of IPE between students from medicine, nursing, physiotherapy, occupational therapy, dietetics, pharmacy and paramedic science, relating to care of stroke patients.…”
Section: Introductionmentioning
confidence: 99%